Neuronal representations of distance in human auditory cortex - Kopčo, Norbert; Huang, Samantha; Belliveau, John W; Raij, Tommi; Tengshe, Chinmayi; Ahveninen, Jyrki (Proceedings of the National Academy of Sciences - PNAS, 2012)
Neuronal mechanisms of auditory distance perception are poorly understood, largely because contributions of intensity and distance processing are difficult to differentiate. Typically, the received intensity increases when sound sources approach us. However, we can also distinguish between soft-but-nearby and loud-but-distant sounds, indicating that distance processing can also be based on intensity-independent cues. Here, we combined behavioral experiments, fMRI measurements, and computational analyses to identify the neural representation of distance independent of intensity. In a virtual reverberant environment, we simulated sound sources at varying distances (15–100 cm) along the right-side interaural axis. Our acoustic analysis suggested that, of the individual intensity-independent depth cues available for these stimuli, direct-to-reverberant ratio (D/R) is more reliable and robust than interaural level difference (ILD). However, on the basis of our behavioral results, subjects’ discrimination performance was more consistent with complex intensity-independent distance representations, combining both available cues, than with representations on the basis of either D/R or ILD individually. fMRI activations to sounds varying in distance (containing all cues, including intensity), compared with activations to sounds varying in intensity only, were significantly increased in the planum temporale and posterior superior temporal gyrus contralateral to the direction of stimulation. This fMRI result suggests that neurons in posterior nonprimary auditory cortices, in or near the areas processing other auditory spatial features, are sensitive to intensity-independent sound properties relevant for auditory distance perception.